1998
DOI: 10.1103/physrevd.58.094034
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of leading particle production

Abstract: Using a QCD-inspired model developed by our group for particle production, the interacting gluon model ͑IGM͒, we have made a systematic analysis of all available data on leading particle spectra. These data include diffractive collisions and photoproduction at DESY HERA. With a small number of parameters ͑essentially only the nonperturbative gluon-gluon cross section and the fraction of diffractive events͒ good agreement with data is found. We show that the difference between pion and proton leading spectra is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…Its original application to the description of inelasticity [12] and multiparticle production processes in hydrodynamical treatments [13] was followed by more refined applications to leading charm production [14] and to single diffraction dissociation, both in hadronic reactions [15] and in reactions originated by photons [16]. These works allowed for providing the systematic description of the leading particle spectra [17] and clearly demonstrated that they are very sensitive to the amount of gluonic component in the diffracted hadron as observed in [18] and [19]. We have found it remarkable that all the results above were obtained using the same set of basic parameters with differences arising essentially only because of the different kinematical limits present in each particular application.…”
Section: A Brief History Of the Igmmentioning
confidence: 99%
“…Its original application to the description of inelasticity [12] and multiparticle production processes in hydrodynamical treatments [13] was followed by more refined applications to leading charm production [14] and to single diffraction dissociation, both in hadronic reactions [15] and in reactions originated by photons [16]. These works allowed for providing the systematic description of the leading particle spectra [17] and clearly demonstrated that they are very sensitive to the amount of gluonic component in the diffracted hadron as observed in [18] and [19]. We have found it remarkable that all the results above were obtained using the same set of basic parameters with differences arising essentially only because of the different kinematical limits present in each particular application.…”
Section: A Brief History Of the Igmmentioning
confidence: 99%
“…The IGM has been described at length, especially in [7] and more recently in [11]. In the past we have successfully modified the IGM in such way as to include in it hadronic single diffractive dissociation processes [9][10][11][12] and applied it to hadronic collisions and HERAphotoproduction data (M 2 X distributions and leading particles spectra of p, π, K and J/ψ).…”
Section: The Igmmentioning
confidence: 99%
“…In what follows, we briefly mention our main formulas. For further discussion we refer to the works [9][10][11].…”
Section: Double Pomeron Exchangementioning
confidence: 99%
See 2 more Smart Citations